CHIARI MALFORMATIONS IN CHILDREN - Peter Spazzapan; Jure Guntar; Borut Prestor (The Society for Children with Metabolic Disorders, 2020)
Background. Chiari malformations represent different clini-cal and radiological clinical entities that share the herniation of the rhomboencephalic structures through the foramen magnum as a common characteristic. Chiari malformations can be symptomatic or asymptomatic. The therapeutic strategies for these malformations differ according to the pathophysiological processes that cause them and the clinical picture. Materials and methods. All paediatric patients with Chiara malformation treated in the Paediatric Neurosurgical Unit of the University Medical Centre Ljubljana between 2015 and 2018 were enrolled. Results. 45 children were treated for a Chiari malformation. 39 had Chiari 1 malformations (CIM) and six had Chiari 2 malformations (CIIM). Nine CIM and one CIIM were treated surgically. Conclusions. Chiari malformations are caused by different pathophysiological processes that must be differentiated to select the best treatment for each single case.